Factor Structure and Item Analysis of the Perceived Quality of Life Scale among People Living with HIV (2013)
The controversy on the operational definitions of quality of life has led to the development of a number of measures which in many cases are culture specific. This study assessed the factor structure and item analysis of perceived quality of life (PQOL) among PLHA in Nigeria. Six hundred and ten PLHA from South West Nigeria participated in the study under condition of anonymity. The perceived quality of life scale and HIV/AIDS-related stigma and discrimination scale were used for data collection. The composite PQOL scale showed high internal consistency with alpha of .923 and standardized alpha of .925, factors analysis revealed four factors (subscales) with eigenvalue before rotation ranging from 1.13 to 8.61 and after rotation from 2.52 to 4.27. Reliability coefficients of the four subscales (affiliation, locus of causality, personal health efficacy and job-family interface) were significant with alpha of. 870, .854, .907, .795 and standardized alpha of .873, .860, .909, and .803 respectively. A divergent validity was established, while the subscales were significantly interrelated. It was concluded that PQOL scale is a valid measure among PLHA and it is a multidimensional construct. Future studies are suggested to investigate the influence and effect of the subscale on the perceived quality of life among PLHA.